1983
DOI: 10.1159/000198867
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Common Bile Duct Stones

Abstract: Common bile duct stones from 59 consecutive patients who underwent cholecystectomy more than 1 year before radiological detection of choledocholithiasis (group I) and from 31 consecutive patients with choledocholithiasis and gallbladder in situ (group II) were subjected to chemical analysis and compared with the composition of gallbladder stones from the same population (two consecutive biopsy and autopsy series, n = 343). In contrast to cholecystolithiasis, inorganic calcium salts were infrequent in choledoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Fifty of these patients had undergone cholecystectomy prior to operative treatment for common bile duct stones. The stones presented here resemble stones reported in these materials [3, 14, 15, 16], but we find an even higher proportion of layered brown pigment stones. The minor part of stones with an easily identifiable structure had cholesterol crystals with a radiating structure.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Fifty of these patients had undergone cholecystectomy prior to operative treatment for common bile duct stones. The stones presented here resemble stones reported in these materials [3, 14, 15, 16], but we find an even higher proportion of layered brown pigment stones. The minor part of stones with an easily identifiable structure had cholesterol crystals with a radiating structure.…”
Section: Discussionsupporting
confidence: 83%
“…In 1964 Bogren [14]published a thorough description of the composition and structure of gallstones, and in 1983 Wosiewitz et al [15]showed that choledocholithiasis in contrast to cholecystolithiasis is characterized by a higher percentage of calculi with large portions of pigment (Ca-bilirubinate). Similar results were found in 96 patients operated for common duct stones [3], of which 53 had cholesterol stones, 42 had pigment stones and 1 stone was unclassified.…”
Section: Discussionmentioning
confidence: 99%
“…(2), while the extraction of cholesterol only can be carried out with isopropylalcohol (3). The measurement of cholesterol is carried out with non-enzymatic (2, 4-7) or enzymatic (3,8) colorimetric methods or by GLC (9,10). Bilirubin can be analysed colprimetrically according to Michaelson (2) or Weber & Schalm (11).…”
Section: Introductionmentioning
confidence: 99%
“…Ca-bilirubinate and black pigment stones are disaggregated in BA-EDTA. These results were confirmed with six CHS, 12 BBIL and 12 BPS from 5 further patients, incubated in the most eligible solvent for any individual stone type.After cholecystectomy common-bile-duct stones are cholesterol stones in about 35% of cases and brown calcium bilirubinate stones in 60-70% [1,2], Approximately 90% of these concretions can be extracted endoscopically [3,4], Of all gallstone patients 10-30% [5][6][7] have black pigment stones in the gall bladder. From here they can migrate into the…”
mentioning
confidence: 99%